Training mental quickness in beginning and intermediate tennis players - Singer, R. N.; Cauraugh, J. H. (The Sport Psychologist, 1994)
Beginner level (undergraduates) tennis players (N = 34) were tested in three tennis situations in a motor learning laboratory and on the court. Ss were divided into two groups: a control group and the other being given supplementary training in mental quickness. Laboratory testing consisted of evaluating direction and type of serves and ground strokes, game situation decisions, and speed and agility reactions to light cues. It was shown that anticipatory skills can be enhanced by appropriate training methods. Speed and accuracy of decisions improved. Only predicting an opponent's ground stroke was not enhanced. Implication: Response times and mechanisms at practice can be improved. Training in an off-court setting can improve beginners. While many studies have shown training procedures for beginners to be inappropriate for advanced and trained individuals, it would not be appropriate to propose this type of training for advanced individuals until its effectiveness has been demonstrated for that population.